2020
DOI: 10.1111/jth.14728
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of postthrombotic syndrome after symptomatic distal deep vein thrombosis: The CACTUS‐PTS study

Abstract: Background After a proximal lower limb deep vein thrombosis (DVT; involving popliteal veins or above), up to 40% of patients develop postthrombotic syndrome (PTS) as assessed by the Villalta scale (VS). Poor initial anticoagulant treatment is a known risk factor for PTS. The risk of developing PTS after isolated distal DVT (infra‐popliteal DVT without pulmonary embolism), and the impact of anticoagulant treatment on this risk, are uncertain. Methods Long‐term follow‐up of CACTUS double‐blind trial comparing 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…The CACTUS-PTS study (2020) studied the long-term effects, after 6 years since the first episode of IDDVT. The results showed an overall PTS incidence of 30%, still considerably less than the reported values for patients after PDVT [27].…”
Section: Post-thrombotic Syndrome (Pts)contrasting
confidence: 62%
“…The CACTUS-PTS study (2020) studied the long-term effects, after 6 years since the first episode of IDDVT. The results showed an overall PTS incidence of 30%, still considerably less than the reported values for patients after PDVT [27].…”
Section: Post-thrombotic Syndrome (Pts)contrasting
confidence: 62%
“…However, it should also be emphasized that distal DVT cannot be free from early and late complications, including pulmonary embolism or post-thrombotic syndrome. In the Contention Alone Versus Anticoagulation for Symptomatic Calf Vein Thrombosis Diagnosed by Ultrasonography (CACTUS PTS) study, the postthombotic syndrome prevalence in patients with isolated calf DVT after median follow-up of 6 years was 30% [39].…”
Section: Discussionmentioning
confidence: 99%
“…16 Although we would no longer be able to randomize anticoagulation against placebo in an acute proximal DVT treatment trial, a recent randomized controlled trial (RCT) included 178 patients with distal DVT and randomized them to either therapeutic LMWH (nadroparin) or placebo for 6 weeks. 17 It showed that in the subgroup of patients without evidence of primary CVI, the rate of PTS at 6 years might be lower when treated with LMWH (9% vs. 24%, p = 0.04); however, this was a subgroup analysis. Current guidelines endorse good-quality anticoagulation as an effective tool for prevention of PTS but do not suggest a specific anticoagulant agent.…”
Section: Effectiveness Of Anticoagulation For Preventing Pts After Dvtmentioning
confidence: 92%